Concept − A relation is an equation if it involves an equal sign.

And if it just involves polynomial function with no equal sign then it's an expression.

Given relation −

\(\displaystyle{\frac{{{1}}}{{{2}}}}{\left({2}{x}-{1}\right)}-{\frac{{{1}}}{{{3}}}}{\left({5}{x}+{2}\right)}={3}\)

Here, we see an equal sign representing the relation. Hence, this is an equation.

Step 2

Let's simplify this equation −

\(\displaystyle{\frac{{{1}}}{{{2}}}}{\left({2}{x}-{1}\right)}-{\frac{{{1}}}{{{3}}}}{\left({5}{x}+{2}\right)}={3}\)

\(\displaystyle{\frac{{{3}{\left({2}{x}-{1}\right)}-{2}{\left({5}{x}+{2}\right)}}}{{{6}}}}={3}\)

\(\displaystyle{3}{\left({2}{x}-{1}\right)}-{2}{\left({5}{x}+{2}\right)}={6}\times{3}\)

6x−3−10x−4 = 18

−4x−7 = 18

−4x = 18+7

−4x = 25

\(\displaystyle{x}=−{\frac{{{25}}}{{{4}}}}\)